Silence after narratives by patients in psychodynamic psychotherapy: a conversation analytic study - Fenner, Carolina (Frontiers in Psychology, 2024)
In psychotherapy, talking is the key activity. Consequently, if the patient remains silent, this may be done in service of different functions, such as thinking about something more deeply, being unwilling to elaborate, etc. This article examines one special environment in which silence occurs conversation analytically: When a patient has closed his/her story, both participants resist the turn allocation by their partner and remain silent instead. The results indicate that both the therapist and the patient produce silence jointly. Therapists end the silence with an intervention, focusing on an aspect of the topic and thereby treating the silence as an intra-topic silence. The study is based on about 29 hours of video recordings of German-speaking outpatient psychodynamic psychotherapies. This paper contributes to increasing therapists' awareness of the various forms of silence that can occur in psychotherapy.